RELATIONSHIP BETWEEN RESPIRATORY MUSCLE STRENGTH AND GRIP STRENGTH IN INSTITUTIONALIZED AND COMMUNITY-DWELLING OLDER ADULTS - Liliane de Faria Marcon; Ruth Caldeira de Melo; Francisco Luciano Pontes Júnior (Brazilian Society of Geriatrics and Gerontology, 2021)
OBJECTIVE: To evaluate the relationship between respiratory muscle strength and grip strength in institutionalized and community-dwelling older adults. METHODS: This convenience sampled cross-sectional study had 64 voluntary participants with a good general health status and without limiting chronic diseases: 33 were institutionalized and 31 lived in the community. Maximal inspiratory pressure, maximal expiratory pressure, peak expiratory flow, grip strength, anthropometric data, and physical activity level were assessed. The data were subjected to descriptive analysis, Pearson's correlation test, and linear regression analysis. RESULTS: In the institutionalized group, there was no between respiratory variables and grip strength, but maximal expiratory pressure was the respiratory predictor most strongly associated with grip strength (p = 0.04). In the community-dwelling group, there was a correlation between maximal inspiratory pressure and grip strength (r = 0.54), maximal expiratory pressure and grip strength (r = 0.62), and peak expiratory flow and grip strength (r = 0.64); peak expiratory flow and maximal expiratory pressure were the respiratory predictors most strongly associated with grip strength (p < 0.05). In a joint group analysis, there was an association between maximal inspiratory pressure and grip strength (r = 0.40), maximal expiratory pressure and grip strength (r = 0.57), and peak expiratory flow and grip strength (r = 0.57); peak expiratory flow and maximal expiratory pressure were the respiratory predictors most strongly associated with grip strength (p < 0.05). CONCLUSIONS: Peak expiratory flow and maximal expiratory pressure seem to be good predictors of grip strength in community-dwelling older adults, but this relationship does not seem to be maintained in institutionalized patients, possibly because of a greater loss of respiratory function.